RENTALIN APPS: Development of a Motorbike Rental Application Using Design Thinking for a Digital Rental Solution - Aulia Salsabilah, Sufia; Harsya; Mentari, Karenia; Monicasari, Shyndy; Wijaya, Hadi (Jurnal Bisnis dan Komunikasi Digital, 2024)
The motorbike rental industry in Indonesia is characterized by significant challenges, including security risks, inefficient operations, and difficulty for customers in finding reliable rental services. This study aims to develop a comprehensive digital solution through the RENTALIN application, which addresses these challenges using a Design Thinking approach. The objective of this research was to create an application that enhances both the operational efficiency for rental owners and the user experience for customers. Data was collected from 13 motorbike rental owners, reported issues such as theft, fraud, and difficulties in tracking motorbikes. Additionally, surveyed customers indicated challenges in finding trustworthy rental services. Based on these findings, the RENTALIN application was designed with features such as GPS-based motorbike tracking, secure data verification systems, and an intuitive user interface. These solutions aim to improve security, expand market reach, and simplify the rental process. Testing of the prototype showed that the application effectively increases the efficiency and safety of the rental process, providing a more seamless experience for both rental owners and customers. RENTALIN demonstrates significant potential to become a leading platform in the Indonesian motorbike rental industry, offering targeted solutions to the sector’s critical issues.